Bi-Sn-Mo-W greisen mineralization associated with the True Hill granite, southwestern New Brunswick - Lentz, David; Lutes, Glenn; Hartee, Ron (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1988)
The Dcvono-Carboniferous True Hill subvolcanic granite porphyry in southwestern New Brunswick forms three granite cupolas along a northeasterly trend. It intruded greenschist-facies argillites of Silurian age, and contains K-feldspar, quartz, plagioclase and biotite phenocrysts in a fine-grained, hypidiomorphic to allotriomorphic granular matrix of similar mineralogy. Metasedimentary xenoliths, narrow metamorphic aureoles along intrusive contacts, miarolilic cavities, pegmatite pods and granophyric texture attest to the upper epizonal nature of the granite. Geochemical constraints indicate a temperature of crystallization of 700°C-730°C, at 100 MPa and less than 1 wt.% fluorine. The True Hill granite is chemically similar to other granites in the Beech Hill series, including the Mount Pleasant fine-grained granite, and to portions of the Eastern Saint George granite batholith. The True Hill granite is weakly peraluminous (A/CNK = 1.6) with a high silica (76.6 wt.%) content. Bi-Sn-Mo-W mineralized zones associated with the cupolas of the True Hill granite are mineralogically similar to but less well developed than W-Mo-Bi mineralization associated with the fine-grained Mount Pleasant granite and the fine-grained portion of the Eastern Saint George granite baiholith. Feldspathic alteration is developed locally in die deeper portions of the True Hill granite, but is inconspicuous in the more intensely altered cupola. Alteration in the cupola includes pervasive and vein quariz-topaz-sericite greisen, quartz-sericite greisen, and quartz-chlorite-sericite greisen in weakly-altered granite. The first two types of greisen contain wolframite (W = 10-60 ppm), molybdenite (Mo = 5-100 ppm) and bismuthinite (Bi = 5->10,000ppm) with low Sn, whereas the third contains cassiterite (Sn = 30-300 ppm) minor pyrite, magnetite and rarely hematite with low Bi, Mo and W. All types of alteration contain fluorite (0.3->2.0 wt.% F). The exogranitic alteration and mineralization is more complex than granite-hosted mineralized zones due to strong compositional control of the metasedimentary rocks on the greisen assemblages.